Texting Protected Health Information in Healthcare. Issue 1 (January 2015) - McCartney, Patricia
<x xml:space="preserve">Abstract</x> Texting protected health information can be quick and convenient, however there is important information nurses need to know to be fully compliant with standards and guidelines from the Health Insurance Portability and Accountability Act (HIPAA), Health Information Technology Economic and Clinical Health Act (HITECH), and National Institute of Standards and Technology (NIST).